Spiritual-Based Transformational Leadership Style at Anutapura Regional General Hospital, Palu - Kolomboy, Fajrillah; Palutturi, Sukri; Rivai, Fridawaty; Saleh, Lalu Muhammad; Masudin, Masudin; Amiruddin, Ridwan (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The leadership style that is considered effective in responding to the challenges of the times as a result of the decline in human values due to the ethical crisis is a spiritual leadership style. The essence of transformational leadership and spiritual leadership is still not being applied by every leader in the organization. AIM: This study aimed to examine the spiritual-based transformational leadership style at Anutapura Regional General Hospital, Palu. METHODS: There were 12 informants in this qualitative research, namely, key informants from top management elements (two people), main informants (four people), supporting informants from Islamic/Christian/Hindu religious figures (three people), community leaders (1 person), and PPNI professional organization (two people). Sources of data were obtained directly through focus group discussions and in-depth interviews. Data analysis was done using NVIVO which was interpreted into a thematic analysis. RESULTS: There were three themes related to the spiritual-based transformational leadership style in this study, those are (1) emotional skills, (2) spiritual skills, and (3) social skills. First, emotional skills consist of emotional skills and emotional intelligence. Second, spiritual skills consist of spiritual attitude and spiritual intelligence. Third, social skills consist of being able to be social. CONCLUSION: This study provides a perception based on an ideal spiritual-based transformational leadership style consisting of three things that affect the patients’ safety culture. It is hoped that the development of this leadership model indicator can be used as a policy approach in implementing a patient safety culture.